2019
DOI: 10.1101/557926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasmid-based CRISPR-Cas9 gene editing in multipleCandidaspecies

Abstract: 22 23

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…This means that the DSBs induced by the CRISPR–Cas9 system are lethal, but can be repaired at low frequency by nonhomologous end joining in C. tropicalis . A similar result, in which only a single base near the cut site was deleted, was recently obtained with a replicating plasmid‐based CRISPR–Cas9 system (Lombardi et al, ). Nonhomologous end joining of DSBs is expected to happen more frequently with plasmid‐based systems.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…This means that the DSBs induced by the CRISPR–Cas9 system are lethal, but can be repaired at low frequency by nonhomologous end joining in C. tropicalis . A similar result, in which only a single base near the cut site was deleted, was recently obtained with a replicating plasmid‐based CRISPR–Cas9 system (Lombardi et al, ). Nonhomologous end joining of DSBs is expected to happen more frequently with plasmid‐based systems.…”
Section: Resultssupporting
confidence: 68%
“…We tried to use the tRNA Ala gene from C. albicans to deliver sgRNA in C. tropicalis , but failed. Recent research has shown that the tRNA Ala gene of Candida parapsilosis can be function in C. tropicalis (Lombardi et al, ). Perhaps this gene might help improve the multi‐gene disruption efficiency of our CRISPR–Cas9 system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…486 487 Tagging Cse4. C. parapsilosis strains CLIB214 and 90-137 were edited using a tRNA 488 plasmid based CRISPR-Cas9 gene editing system as described byLombardi et al 489 (Lombardi et al 2017, 2019a. Primers gRNA_CSE4_TOP and gRNA_CSE4_BOT were 490annealed and cloned into pCP-tRNA and 5 µg plasmid was transformed together with 5 µg 491 of a 594 bp synthetic DNA fragment containing a section of the H3 histone variant Cse4 with 492 a 3xHA (hemagglutinin) tag inserted between amino acids 69 and 70, and 250bp homology 493 arms (Integrated DNA Technologies USA, Supplemental_Fig._S1).…”
mentioning
confidence: 99%